2014
DOI: 10.1016/j.etp.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

N-diethylnitrosamine mouse hepatotoxicity: Time-related effects on histology and oxidative stress

Abstract: Animal models, namely mice, have been used to study chemically induced carcinogenesis due to their similarity to the histological and genetic features of human patients. Hepatocellular carcinoma (HCC) is a common malignancy with poor clinical outcome. The high incidence of HCC might be related to expo-sure to known risk factors, including carcinogenic compounds, such as N-nitrosamines, which cause DNA damage. N-nitrosamines affect cell mitochondrial metabolism, disturbing the balance between reactive oxygen sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Assay was conducted as described by Paula Santos et al [23]. The reaction medium consisted of potassium phosphate buffer (50 mM KH 2 PO 4 pH 7.4) and H 2 O 2 (1 M) in a final volume of 1 ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assay was conducted as described by Paula Santos et al [23]. The reaction medium consisted of potassium phosphate buffer (50 mM KH 2 PO 4 pH 7.4) and H 2 O 2 (1 M) in a final volume of 1 ml.…”
Section: Methodsmentioning
confidence: 99%
“…The GR activity was performed according to Paula Santos et al [23] and Smith et al [24]. The reaction medium consisted of potassium phosphate buffer (100 mM KH 2 PO 4 and 0.5 mM EDTA, pH 7.4), 100 mM GSSG, and 10 mM NADPH.…”
Section: Methodsmentioning
confidence: 99%
“…The diethylnitrosamine (DEN)-induced HCC in mouse is one of the most frequently used animal models in liver cancer researches89, which has a gene expression profile similar to human HCC10. The formation of alkyl DNA adducts, which causes genome instability, and eventually results in the transformation of preneoplastic or neoplastic cells, has been considered as the key event in DEN-mediated tumorigenesis111213.…”
mentioning
confidence: 99%
“…DEN caused cellular oxidative stress and DNA damage through inhibiting the mitochondrial metabolism and augmenting the release of reactive oxygen and nitrogen species (ROS and RNS, respectively). Therefore, the generation and accumulation of free radicals by DEN played a major role in the development of HCC . In the current study, the concentration of liver nonenzymic antioxidants (GSH) and the activities of liver enzymic antioxidants (CAT, GPx, and SOD) decreased significantly in the DEN‐induced hepatocarcinogenic mice compared with the noncancerous control mice, which likely led to hepatic oxidative injury.…”
Section: Discussionmentioning
confidence: 57%
“…In the current study, the concentration of liver nonenzymic antioxidants (GSH) and the activities of liver enzymic antioxidants (CAT, GPx, and SOD) decreased significantly in the DEN‐induced hepatocarcinogenic mice compared with the noncancerous control mice, which likely led to hepatic oxidative injury. Other studies also reported the defects in hepatic antioxidant defense system of rodents due to the excessive production of ROS by DEN . ROS oxidizes cellular fatty acids, especially polyunsaturated fatty acids, and produces lipid peroxyl radicals.…”
Section: Discussionmentioning
confidence: 92%